Structural and Electronic Properties of Intercalated Transition Metal Dichalcogenides Compounds - Parmar, Vandana B.; Vora, Aditya M. (BIBECHANA, 2022)
The structural and electronic properties of Transition Metal Dichalcogenides Compound (TMDC) TiS2 and its intercalated compound like FeTiS2 are reported in the present work using Density Functional Theory (DFT). The Generalized Gradient Approximation (GGA) with ultrasoft pseudopotential are used under Quantum ESPRESSO code. From the theoretical data, it is concluded that, the energy band structure of the TiS2 material has been a small indirect band gap and possess a semiconductor characteristic. While the doped intercalated compound like FeTiS2, the energy bands are overlapped in the Fermi region, which possess metallic characteristics. Also, FeTiS2 is a ferromagnetic material with spin up and spin down nature observed from the band structure data. BIBECHANA 19 (2022) 97-101